Behaviour of reinforced concrete-ferrocement composites - Hossain, Mahmood; Pama, Ricardo P.; Ogunlana, Stephen O.; Pichai Nimityongskul; DAAD (Bangkok : Asian Institute of Technology, 1991)
The flexural behaviour of six composite beams made of low strength concrete and encased in U-shaped ferrocement forms made of high strength mortar reinforced with square welded wire mesh, were compared with two reference beams by conducting flexural tests under two symmetrical point loads, in simply supported conditions. This study deals with an experimental and analytical investigation of the ultimate moment capacity, first cracking moment, ultimate shear load capacity and deformational behaviours of these beams. The only variable parameter of this study was the number of layers of wire mesh used in the fer rocement form. The scope was to determine the effect of the wire mesh and the skeletal steel bars as flexural reinforcement and shear force reinforcement. In computing the ultimate moment capacities of the composite beams, conventional reinforced concrete theory was used. The test results are in good agreement with the calculated moments, shears and deformations. They also show that the wire mesh is fully effective and a full composite action between the ferrocement form and the core concrete is attained up to failure load.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1991
Keywords: Ferrocement; Composite construction